PREFERENSI KONSUMEN MINYAK GORENG CURAH DAN BERMERK PADA RUMAH TANGGA PEDESAAN DI KABUPATEN JEMBER: SEBUAH ANALISIS MULTIATRIBUT FISHBEIN - Wulandari, Savira Putri; Zainuddin, Ahmad (JURNAL AGRIMANSION, 2023)
Jember Regency has a high level of ethnic diversity with dominant Javanese and Madurese. The emergence of phenomena such as the mandatory packaging of cooking oil policy, price increases and scarcity of cooking oil affect consumer consumption habits and patterns. The purpose of the study was to determine consumer preferences for cooking oil attributes in rural households in Jember Regency. The research was conducted in Jember Regency with sample sub-districts of Wuluhan, Ambulu, Kalisat, and Arjasa. The sample used was 120 respondents with a division of 30 respondents per sub-district. The research was analyzed through fishbein multiattribute analysis. The results of the analysis show that consumer preferences favor branded cooking oil with a preference value of 70.99 and a positive attitude category. The attributes of branded cooking oil that are considered superior include packaging shape, color, purchase size, branded cooking oil type, coconut oil type, traditional market, modern market, transportation, explanation, organic certification, promotion, 1 liter cooking oil packaging, cooking oil packaging > 1 liter, brand, filtering process, and halal label. Producers should hold promotions in the form of discounts and further increase the production of branded cooking oil because it tends to be preferred by consumers. In addition, the government needs to provide incentives to producers who use healthier production methods so that they can become examples for other producers.